(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
It is worth mentioning that the high output of different physiological responses under the expression of vgb, may have a considerable effect on the enzyme productivity, dairy industry, heavy metal uptake, biodegradation of different organic pollutants and other applications. The expression of bacterial haemoglobin is useful in lessening the load of perceived toxic conditions such as high oxygen levels. This in turn probably has the same impact on some peripheral toxic materials. This, hemoglobin biotechnology can be extended to enhance production of pollutants degrading enzymes or production of some valuable manufacturing materials on the case-by-case bases. It is likely that the mechanism of bacterial hemoglobin (VHb) effects is intermediated via an oxygen trapping action. This may drive the enrichment of ATP production, which is mostly required for higher productivity of needed substances for that activity.